DEVELOPING SPEAKING SKILL OF THE THIRD SEMESTER STUDENTS OF TBI FTIK IAIN PALU THROUGH TABLEMATE INTERVIEW - Marzuki, Abdul Gafur; Fitriningsih, Fitriningsih (Paedagogia: Jurnal Pendidikan, 2017)
The research aims at Developing Speaking Skill of the Third Semester Students of TBI FTIK IAIN Palu through Tablemate Interview. The subject of the research was the third semester consisted of 24 students of TBI FTIK IAIN Palu. The research was classroom action research which was conducted in two cycles where each cycle consisted of planning, implementation, observation and reflection. The data of this research were obtained from the results of the test and observation sheet, field notes, during the implementation of the action. The findings of the research showed that Tablemate Interview was effective in developing students’ speaking skill. The effectiveness of Tablemate Interview was shown by the improvement of students’ score. The findings revealed that in cycle 1 there were thirteen students who achieved minimum criteria of achievement. It means that the classical achievement was 54.16%. In cycle 2, it found that there were twenty four or all students who achieved the minimum criteria of achievement. It means that the gained achievement was 100%. Gained achievement is based on the number of students who got the score at least the criteria of success (65). Both of the gained and individual achievements have met the criteria of success. It can be concluded that the Tablemate Interview was effective to develop the students’ speaking skill.